Social media, diffusion of innovations, morale and digital inequality : A case study at the University of Limpopo Libraries, South Africa - Williams, Marion Lucille; Dhoest, Alexander; Saunderson, Ian (Library Hi Tech, 2019)
Purpose – The purpose of this paper is to explore social media usage in an academic library in South Africa and the factors influencing its use. The primary goal of the study was to examine perceptions surrounding the impact of non-adoption of social media on morale, and to explore the consequences of digital inequality. Design/methodology/approach – Using a qualitative method, in-depth interviews were conducted with a small sample comprising six key informants at the University of Limpopo Libraries. Findings – The findings suggest that non-adoption of social media has a negative influence on morale, and that it is a very necessary tool required for interaction with students as well as promotion and marketing of the library’s resources. Research limitations/implications – This paper is limited to one academic library in South Africa situated in a rural area. The research suggests that more academic libraries in rural areas be studied to ascertain if geographical location and finance are barriers to social media adoption. Originality/value – This study addresses non-adoption of social media and suggests ways to improve employee morale and retention. The research contributes to current research.
Article published in the Library Hi Tech Vol. 37 No. 3, 2019 pp. 480-495
Keywords: Academic libraries; Social media; Digital divide; Environmental factors; Employee morale; Non-adoption; Digital media - Social aspects; Online social networks; Social media in education; Academic libraries --South Africa